KESIAPAN INDONESIA UNTUK MELAKSANAKAN REHABILITASI BAGI PENYALAHGUNA NARKOTIKA DILIHAT DARI PERSPEKTIF ANGGARAN - Ratna Christianingrum; Tio Riyono; Leo Iskandar (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2023)
Narcotics abusers in Indonesia can be sentenced to imprisonment, rehabilitation, or other punishments in accordance with Law Number 35 of 2009 concerning narcotics. The courts have not maximized rehabilitation and still impose prison sentences for narcotics users in Indonesia. This research analyzes secondary data in the form of data on the prevalence of narcotics use from 2008 to 2021, the number of residents aged 15–64 years, and the number of rehabilitation and rehabilitation budgets. The method used is to forecast through trend comparison, mean, and cubic trend analysis, then calculate budget requirements and compare them with budget requirements. Subsequently, a readiness analysis for the budget is conducted by comparing the projected rehabilitation budget needs with the projected budget availability. The research results show that the ratio of the need for rehabilitation places to the availability of rehabilitation facilities is high. The budget availability for rehabilitating narcotics abusers is still insufficient, and the budget requirement for rehabilitating narcotics users in 2024 will reach IDR102 trillion. This budget equals 387 times the budget for the BNN Narcotics Rehabilitation Center in 2022. The results of this research show that the government is not yet ready to carry out ideal narcotics rehabilitation. For this reason, public-private partnerships (PPP) in terms of providing rehabilitation facilities can be a policy solution for fulfilling the availability of rehabilitation places for narcotics abusers.